Pengaruh Kualitas Layanan Dan Kepuasan Terhadap Loyalitas Pelanggan Pada Pengguna Jasa Ekspedisi Paxel Home Jakarta Timur - Hermawan, Rudianto; Saifullah, Saifullah; Kusyeni, Raden; Sobari, Indra Soemarna; Handayani, Risky (JAMBIS : Jurnal Administrasi Bisnis, 2025)
This study aimed to evaluate the effect of Service Quality and Customer Satisfaction variables on Customer Loyalty among users of Paxel Home expedition services in East Jakarta. Data were collected through questionnaires distributed to 130 respondents and processed using the IBM SPSS Statistics 26 program. The recapitulation results showed that the average Service Quality and Customer Satisfaction variables were 4.32 each, and the average Customer Loyalty variable was 4.28, all of them were in the ˜Strongly Agree’ or ˜Excellent’ category. The sample was determined using the Hair et al (2010: 101) formula and a total of 130 people were obtained, so the respondents used in this study were unlimited people. The analysis was carried out by testing the Coefficient of Determination, Multiple Linear Regression, and t-test to measure how much influence the independent variables (Service Quality and Customer Satisfaction) have on the dependent variable (Customer Loyalty). The results of the calculation of the Coefficient of Determination (R2) showed that 64.6% of the variation in Customer Loyalty could be explained by Service Quality and Customer Satisfaction, while35.4% was influenced by other variables not examined. The t-test showed that the variables of Service Quality (X1) and Customer Satisfaction (X2) each had a significant effect on Customer Loyalty (Y), with a t-count value for Service Quality of 13.713 (p < 0.05) and for Customer Satisfaction of 10.584 (p < 0.05). The results showed that Service Quality and Customer Satisfaction significantly affect Customer Loyalty